Social Costs of Obesity in the Czech Republic - Petra Landovska (Charles University in Prague, Institute of Economic Studies (IES), 2021)
Increasing prevalence of obesity is a pressing public health issue in the Czech Republic as well as world-wide, affecting up to 2.1 billion people. In the Czech Republic, 20-25% of adults and an increasing number of children are obese now. Given that obesity is a chronic disease which is associated with several serious comorbidities, it generates large social costs. The main aim of this study was to estimate both direct and indirect costs of obesity in the Czech Republic. Social costs of obesity are estimated using the cost-of-illness approach. Population attributable fractions (PAF) are computed based on prevalence of obesity in the Czech Republic and relative risks of 19 comorbidities. Direct costs (healthcare utilization costs and costs of pharmacotherapy) are estimated using the top-down approach, while indirect costs (absenteeism, presenteeism and premature mortality) are estimated using the human capital approach. In aggregate, the annual costs attributable to obesity in the Czech Republic in 2018 were 37.3 billion CZK (1.5 billion EUR). Direct costs were 13.1 billion CZK (0.5 billion EUR) and accounted for 3% of Czech healthcare expenditures. The highest healthcare utilization costs were attributable to type II diabetes (21.7%), ischemic heart disease (18.4%) and osteoarthritis (16.9%). The largest indirect costs were attributable to premature mortality (9.2 billion CZK/0.36 billion EUR), absenteeism (8.7 billion CZK/0.34 billion EUR) and presenteeism (6.3 billion CZK/0.25 billion EUR). This report demonstrates that obesity is a serious problem with considerable costs. Several preventive interventions should be applied in order to decrease the prevalence of obesity and achieve cost savings.
Keywords: I12; I18; 330; obesity; social costs; cost-of-illness study; Czech Republic